ANALISIS YURIDIS TERHADAP TINDAK PIDANA KORUPSI YANG MENERIMA HADIAH KARENA KEKUASAAN (Studi Putusan Nomor : 85/Pid.Sus-TPK/2024/PN Bdg) - Maulana Hasanudin; Syahrul Anwar; Suradi (Jurnal Riset Multidisiplin Edukasi, 2025)
Corruption has become an issue that erodes public trust in government institutions in Indonesia. According to Transparency International, Indonesia ranks 102nd out of 180 countries in the 2022 Corruption Perceptions Index (CPI), indicating that much work remains to be done to eradicate corruption (Transparency International, 2022). In this context, the legal provisions regarding criminal acts of corruption are regulated in Law No. 31 of 1999, which was later amended by Law No. 20 of 2001, which regulates the Eradication of Criminal Acts of Corruption. This article will provide a legal analysis of criminal acts of corruption involving civil servants who accept gifts because of their power. Using the case of Defendant Regi Artaputrawan at the Bandung District Court with Case Number 85/Pid.Sus-TPK/2024/PN Bdg as a case study, this analysis will discuss the public prosecutor's indictment and the judge's verdict, as well as the implications of these decisions for law enforcement and anti-corruption policies in Indonesia. Through a legal analysis approach, it is hoped that this study will provide a clear picture of the challenges and solutions in eradicating corruption in Indonesia.